Change in patient-reported outcomes in patients with and without mechanical symptoms undergoing arthroscopic meniscal surgery: A prospective cohort study. Issue 8 (August 2018) - Pihl, K.; Turkiewicz, A.; Englund, M.; Lohmander, L.S.; Jørgensen, U.; Nissen, N.; Schjerning, J.; Thorlund, J.B.
Summary: Objective: Patients with degenerative or traumatic meniscal tears are at high risk of developing knee osteoarthritis. We investigated if younger (≤40 years) and older (>40 years) patients with preoperative mechanical symptoms (MS) improved more in patient-reported outcomes after meniscal surgery than those without MS. Design: Patients from Knee Arthroscopy Cohort Southern Denmark (KACS) undergoing arthroscopic surgery for a meniscal tear completed online questionnaires before surgery, and at 12 and 52 weeks follow-up. Questionnaires included self-reported presence of MS (i.e., sensation of catching and/or locking) and the Knee injury and Osteoarthritis Outcome Score (KOOS). We analyzed between-group differences in change in KOOS4 from baseline to 52 weeks, using an adjusted mixed linear model. Results: 150 younger patients (mean age 31 (SD 7), 67% men) and 491 older patients (mean age 54 (SD 9), 53% men) constituted the baseline cohorts. Patients with MS generally had worse self-reported outcomes before surgery. At 52 weeks follow-up, younger patients with preoperative MS had improved more in KOOS4 scores than younger patients without preoperative MS (adjusted mean difference 10.5, 95% CI: 4.3, 16.6), but did not exceed the absolute postoperative KOOS4 scores observed for those without MS. No difference in improvement was observed between older patients with or without MS (adjusted mean difference 0.7, 95% CI: −2.6, 3.9). Conclusions: Younger patients (≤40 years) with preoperative MS experienced greater improvements after arthroscopic surgery compared to younger patients without MS. Our observational study result needs to be confirmed in randomized trials.